Fluid Mechanics in SI Units / Fundamentals and Applications: Third Edition in SI Units - Cengel Yunus A; Cimbala John M (Mc Graw Hill Education, 2015)
This book covers the basic principles and equations of fluid mechanics in the context of numerous and diverse real-world engineering examples. Preface, Introduction and Basic Concepts, Properties of Fluids, Pressure and Fluid Statics, Fluid Kinematics, Bernoulli and Energy Equations, Momentum Analysis of Flow Systems, Dimensional Analysis and Modeling, Internal Flow, Differential Analysis of Fluid Flow, Approximate Solutions of the Navier-Strokes Equation, External Flow: Drag and Lift, Compressible Flow, Turbomachinery, Introduction to Computational Fluid Dynamics, Glossary, Index.